A Social Learning Approach for Stakeholder Engagement in Large Carnivore Conservation and Management - Hovardas, Tasos (Frontiers in Ecology and Evolution, 2020)
The present paper reports on a methodology for stakeholder engagement in large carnivore conservation and management, which was implemented in a LIFE project in Greece (LIFE-AMYBEAR: Improving Human-Bear Coexistence Conditions in Municipality of Amyntaio -LIFE15 NAT/GR/001108). The methodology was employed within the frame of human dimensions actions in that project and included three different stages planned in a modular sequence (stakeholder analysis; stakeholder consultation and involvement; participatory scenario development). Each stage was operationalized by means of a template (Strengths, Weaknesses, Opportunities and Threats Analysis template; mixed-motive template; template for participatory scenario development), which was designed to structure stakeholder input and interaction and scaffold social learning. The templates were completed by standard methods and procedures in social science, namely, interviews, focus groups, and workshops. The presentation of the methodology in this paper has a demonstration character. The main aim is to showcase its heuristic value in steering stakeholder collaboration and tracking change as a result of stakeholder joint action. The paper will demonstrate the benefits and added value of innovation and change initiated by actions in the LIFE project, as well as the costs or unintended consequences of that innovation and change, which need to be tackled by future stakeholder collaboration. The beginnings of an institutionalization of stakeholder involvement revealed features of both formal (e.g., new institutions established such as a Bear Emergency Team) and informal institutions (e.g., social norms). These features illustrated a departure from the current condition, where social learning may be already traceable. At the same time, however, stakeholder interaction has also delineated additional aspects that need to be addressed by stakeholders. The added value of the methodology is that it can be enacted by stakeholders themselves, provided that they are empowered to take ownership of the social learning process. Therefore, it can be exploited in after-LIFE plans. The approach can also be used in other multi-stakeholder arrangements, such as platforms concentrated on wildlife conservation and management. Finally, it should be noted that the methodology and templates fill an important gap, often highlighted in the social learning literature, in that they offer a toolkit for monitoring and assessment.